The economic cost of losing native pollinator species for orchard production. Issue 3 (19th January 2020) - Pérez‐Méndez, Néstor; Andersson, Georg K. S.; Requier, Fabrice; Hipólito, Juliana; Aizen, Marcelo A.; Morales, Carolina L.; García, Nancy; Gennari, Gerardo P.; Garibaldi, Lucas A.
Abstract: The alarming loss of pollinator diversity world‐wide can reduce the productivity of pollinator‐dependent crops, which could have economic impacts. However, it is unclear to what extent the loss of a key native pollinator species affects crop production and farmer's profits. By experimentally manipulating the presence of colonies of a native bumblebee species Bombus pauloensis in eight apple orchards in South Argentina, we evaluated the impact of losing natural populations of a key native pollinator group on (a) crop yield, (b) pollination quality, and (c) farmer's profit. To do so, we performed a factorial experiment of pollinator exclusion (yes/no) and hand pollination (yes/no). Our results showed that biotic pollination increased ripe fruit set by 13% when compared to non‐biotic pollination. Additionally, fruit set and the number of fruits per apple tree was reduced by less than a half in those orchards where bumblebees were absent, even when honeybees were present at high densities. Consequently, farmer's profit was 2.4‐fold lower in farms lacking bumblebees than in farms hosting both pollinator species. The pollination experiment further suggested that the benefits of bumblebees could be mediated by improved pollen quality rather than quantity. Synthesis and applications . This study highlights the pervasive consequences of losing key pollinator functional groups, such as bumblebees, for apple production and local economies. Adopting pollinator‐friendly practices such as minimizing the use of synthetic inputs or restoring/maintaining semi‐natural habitats at farm and landscape scales, will have the double advantage of promoting biodiversity conservation, and increasing crop productivity and profitability for local farmers. Yet because the implementation of these practices can take time to deliver results, the management of native pollinator species can be a provisional complementary strategy to increase economic profitability of apple growers in the short term. Abstract : This study highlights the pervasive consequences of losing key pollinator functional groups, such as bumblebees, for apple production and local economies. Adopting pollinator‐friendly practices such as minimizing the use of synthetic inputs or restoring/maintaining semi‐natural habitats at farm and landscape scales, will have the double advantage of promoting biodiversity conservation, and increasing crop productivity and profitability for local farmers. Yet because the implementation of these practices can take time to deliver results, the management of native pollinator species can be a provisional complementary strategy to increase economic profitability of apple growers in the short term. Resumen: La alarmante pérdida de polinizadores que acontece a escala global puede reducir la productividad y el potencial económico de muchos cultivos entomófilos (p.ej. frutales). Sin embargo, aún no está claro hasta qué punto la pérdida de una única especie (o grupo funcional) puede afectar al rendimiento del cultivo y al beneficio económico del agricultor. Se manipuló experimentalmente la presencia de una especie de abejorro nativo Bombus pauloensis en ocho fincas de manzano en el sur de Argentina, para evaluar cómo la pérdida de las poblaciones nativas de este grupo de polinizadores (abejorros) afecta a (a) el rendimiento del cultivo, (b) a la calidad de la polinización y (c) al rendimiento económico del cultivo. Para ello, llevamos a cabo además un experimento factorial de exclusión de polinizadores (sí/no) y suplemento manual de polen (sí/no). Nuestros resultados muestran que la polinización biótica, es decir mediada por polinizadores, incrementó el cuajado de frutos maduros en un 13% respecto a la polinización abiótica (sin polinizadores). Además, el cuajado y el número de frutos por manzano se redujo a más de la mitad en aquellas fincas donde, a pesar de que la abeja de la miel estaba presente en altas densidades, el abejorro nativo estaba ausente. Como consecuencia, el beneficio económico para el agricultor en estas fincas fue 2.4 veces menor que en aquellas donde la abeja de la miel y el abejorro nativo estaban presentes simultáneamente. Nuestro experimento sugiere que la mejora del rendimiento aportada por los abejorros nativos está mediada por una mejora en la calidad del polen más que por un incremento en la cantidad. Síntesis y aplicaciones . Este estudio muestra las consecuencias negativas que van emparejadas a la pérdida de grupos de polinizadores clave, como los abejorros, en la producción de manzana y en el beneficio económico del agricultor. La adopción de prácticas agrícolas amigables con los polinizadores, como la reducción de agroquímicos o la restauración y mantenimiento de hábitats seminaturales a escala local y a escala de paisaje, se espera que tenga la doble ventaja de promover, por un lado, la conservación de la biodiversidad y, por otro, incrementar la productividad y el rendimiento económico para los productores. Dado que estas prácticas pueden tardar un tiempo en dar resultados, el manejo de especies nativas de polinizadores puede ser una estrategia provisional y complementaria para reducir, a corto plazo, el impacto económico para el agricultor.